Housing policy responses to COVID-19 - Rowley, Steven (2020)
The COVID-19 pandemic created an unprecedented crisis facing the housing system and the people who depend upon it. So large was the potential risk arising from the crisis, that a comprehensive and coordinated, whole-of government response was required. In this new AHURI webinar, we presented the findings from two new research projects examining housing policy responses to COVID-19.